The need for a more ambitious structure of governance to face new challenges within the EU - Bilbao-Ubillos, Javier (Frontiers in Political Science, 2025)
Neo-functionalism, intergovernmentalism and a political economy of national self-interest have characterised a process of European integration that was strongly oriented towards the full realisation of the three freedoms. The construction of the EU was centred on taking advantage of the allocative benefits of the market, without great pretensions in other fields. The subsequent pressing need to give the project a social dimension, to act as a key global actor in foreign affairs and defence, and to jointly tackle economic, financial, health and protectionist crises has faced severe limitations due to the lack of sufficient automatic response instruments, the complicated decision-making process, mistrust between Member States and the temptation to seek individual solutions to threats. A new and more ambitious structure of governance is needed to promote agility and ensure that the measures adopted are in line with the interests and values of citizens.